Physics of biological action and perception - Latash, Mark L., 1953- (Academic Press, 2020)
Physics of Biological Action and Perception helps researchers interested in exploring biological motor control from a physics or alternative viewpoint perspective. The book introduces the idea of parametric control as a distinguishing feature of living systems. Sections cover how the CNS creates stable percepts based on fuzzy and continuously changing signals from numerous receptors and the variable processes related to ongoing actions. The author also develops the idea of control with referent coordinates to stability of salient variables in fields typically united under the label of "cognition." Examples of this include communication (how the gist of a message is preserved despite variability of phrases), thought processes (how one can solve a mental problem via different logical routes), and playing chess (how one selects an optimal move given a position on the board). The book is written for researchers, instructors, clinicians and other professionals in all the fields related to biological movement and perception.